The Diversity of Vegetable Dishes in Mandailing Culinary - Esi Emilia; Onggal Sihite; Adikahriani Adikahriani; Nila Reswari Haryana; Siti Sutanti; Risti Rosmiati; Subuh Ardiansyah; Hardi Firmansyah (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
Culinary is one of the cultural products of various ethnicities in Indonesia. One of the famous culinary in North Sumatra is culinary of the Batak Mandailing. This study aims to identify vegetable dishes in Mandailing Culinary and processing techniques. The research was conducted from April -November 2021 in Mandailing Natal Regency. The data was collected qualitatively by conducting FGD and in-depth interviews method. The Location of Mandailing Natal Regency is in the southernmost and western part of the province of North Sumatra so that the taste of Mandailing cuisine is influenced by cuisine from Minangkabau. The availability of food, in terms of vegetables, spices, and coconut, is abundantly reflected in the various types of vegetables in daily meals of the Mandailing Natal people. Mandailing’s vegetable dishes dominantly have a spicy taste and uses a lot of coconut or coconut milk and also wet and dry spices. The study results found that 53 types of vegetable dishes were dominated by curry dishes using many spices. Mashed cassava leaves curry is one of the popular vegetable dishes. Most of the Mandailing cuisine uses high-temperature processing technology, especially the boiling method.